Adaptive functional differentiation of dendritic cells: integrating the network of extra- and intracellular signals - Luft, Thomas; Rodionova, Elena; Maraskovsky, Eugene; Kirsch, Michael; Hess, Michael; Buchholtz, Christian; Görner, Martin; Schnurr, Max; Skoda, Radek; Ho, Anthony Dick (Blood, 2006)
Phenotypic maturation, cytokine secretion, and migration are distinct functional characteristics of dendritic cells (DCs). These functions are independently regulated by a number of extracellular variables, such as type, strength, and persistence of an array of soluble and membrane-bound mediators. Since the exact composition of these variables in response to infection may differ between individuals, the intracellular signaling pathways activated by these extracellular networks may more closely correlate with DC function and predict the course of adaptive immunity. We found that activation of p38 kinase (p38K), extracellular signal-related kinase 1/2 (ERK1/2), and phosphatidylcholine-specific phospholipase C (PC-PLC) enhanced cytokine secretion, whereas p38K, cyclic adenosine monophosphate (cAMP), and PC-PLC enhanced migration. In contrast, phosphatidylinositol 3-kinase (PI3K)/Akt-1 and cAMP inhibited cytokine secretion while ERK1/2 inhibited migration. Migration and cytokine secretion further differed in their sensitivity to inhibition over time. However, although DCs could be manipulated to express migration, cytokine secretion, or both, the level of activation or persistence of intracellular pathway signaling was not predictive. Our results suggest a modular organization of function. We hypothesize that the expression of specific DC functions integrates a large variety of activating and inhibitory variables, and is represented by the formation of a functional unit of molecular networks—the signal response module (SRM). The combined activities of these modules define the functional outcome of DC activation.
Gesehen am 22.11.2021